LITERASI LAPORAN KEUANGAN IBU-IBU WIROGUNAN YOGYAKARTA - Jajuk Herawati; Siti Sumartiah; Pristin Prima Sari; Destri Wulandari (Jurnal Kewirausahaan dan Bisnis, 2020)
Financial reports become useful for every business actor and family because of financial information sources. Most of the Wirogunan women have little knowledge in making business financial reports so that training in financial reporting being valuable to disseminate for business people and families. This community service activity aims to provide training on financial reports to Wirogunan Yogyakarta women. The methods of activity are lectures, question-and-answer, and financial reporting practice. The results showed that increasing knowledge of financial reports for Women in Wirogunan. The benefit of this activity is that Wirogunan Yogyakarta women can be orderly in making small business financial reports. The output of this dedication is a small business financial report booklet.Keywords: community services, financial reports, literation